1996
DOI: 10.1016/0014-5793(96)00262-1
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of rat liver CMP‐N‐acetylneuraminate:GM1 sialyltransferase (SAT IV) activity on the ceramide composition of GM1 ganglioside

Abstract: The dependence of CMP-N-acetylneuraminate:GMl sialyltransferase (SAT IV) activity of rat liver Golgi apparatus on GM1 ganglioside ceramide composition was evaluated. SAT IV activity was assayed on GMI molecular species carrying homogeneous ceramide moieties containing long chain bases of different length (18 or 20 C atoms) unsaturated or not, linked to 14:0, 16:0, 18:0 or 22:0 fatty acids. The results obtained in the presence of the detergent Triton CF-54, when enzyme and substrate are presumably part of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…In general, most of the investigations concerning gangliosides take into account only their oligosaccharide moiety, even if several studies show that also the ceramide moiety changes throughout animal life (Ando and Yu, 1984;Palestini et al, 1990Palestini et al, , 1991b) and can play a relevant biological role (Masserini et al, 1988(Masserini et al, , 1989Palestini et al, 1991a;Pitto et al, 1996). For this reason, the LCB and the fatty acid composition of gangliosides in the two hemispheres were analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…In general, most of the investigations concerning gangliosides take into account only their oligosaccharide moiety, even if several studies show that also the ceramide moiety changes throughout animal life (Ando and Yu, 1984;Palestini et al, 1990Palestini et al, , 1991b) and can play a relevant biological role (Masserini et al, 1988(Masserini et al, , 1989Palestini et al, 1991a;Pitto et al, 1996). For this reason, the LCB and the fatty acid composition of gangliosides in the two hemispheres were analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it has been suggested that a key role is played by the predetermined distribution of C 18-and C20-sphinganines that is related to the kinetic properties of the enzyme acyl-CoA:serine acyltransferase (Chigorno et al,i994). Moreover, concerning the biosynthesis of glycosphingolipids, it has been shown that sialyltransferases are able to recognize different molecular species of the substrate, providing a mechanism aimed at maintaining the glycolipid ceramide pattern of a given tissue or cell situation (Kadowaki and Grant, 1995;Pitto et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…N -acetyl- l -histidine had the lowest content among all down-regulated amino acids. Studies have shown that this substance can catalyze the synthesis of gangliosides [ 44 ], and high levels of certain specific gangliosides can lead to many genetic diseases. The significant decrease of N -acetyl- l -histidine in fermented camel milk indicated that fermented camel milk can effectively reduce the occurrence of many genetic diseases.…”
Section: Discussionmentioning
confidence: 99%